Developmental Post-Conflict Reconstruction in Postindependence Nigeria: Lessons From Asian Developmental States. Issue 3 (December 2021) - Ikpe, Eka
Post-conflict reconstruction (PCR) has come away from a dynamic reading of the role of the state within contemporary reflections on peacebuilding. This article introduces the framework of developmental PCR that draws on the developmental state paradigm to offer a lens for understanding the role of the state and its complex interlinkages with other milieus such as the market in PCR. Developmental PCR is premised on three tenets: interdependence between economic development and security; the importance of state–market interdependencies within industrial development, as reconstruction; and how characterisations of statehood interact with reconstruction. The deployment of developmental PCR in the case study of the Nigerian Civil War illuminates certain realities such as the significance of economic nationalism to security, complex interdependencies across the state and market that underpinned key elements of industrial policy during reconstruction, and the nuances in the characterisation of the Nigerian state as strong on account of military regimes.